The legal and regulatory challenges of making e-transactions a defining part of the Lebanese economy - Halabi, Mirna (2021)
With the simple push of a button, billions of dollars in commerce are exchanged throughout the globe on a daily basis. Today, electronic money transfer services (EMT) have reduced transaction costs for the general public, enabled business growth through ecommerce, and created a universal payments system that helps everyone, except Lebanese people. Although numerous services in Lebanon are lacking in technological development, the reason for the lack of progress in Lebanon's EMT services is due to decades of market dominance and protectionism that has inflated the cost of service. The main objective of the research is to dress the legal framework of electronic money transfers in Lebanon, and the fundamental responsibility of the Central Bank of Lebanon as a regulator in this field. Legislation allowing electronic money transfers was finally passed by Lebanon's parliament on November 10, 2018 after a 20-year period in which Lebanon's financial regulatory structure was unable to keep pace with advanced financial technology because of a severe absence of coherence in the process of strategic financial planning. However, even though we had high hopes as Lebanese consumers that Lebanon will finally benefit from the consequences of a liberal financial vision, the impact of this law–unfortunately- did not meet the standards that we were hoping for. In this respect, I am seeking through this research to highlight the fragilities and loopholes in the Lebanese legal framework and regulatory and propose modern recommendations for the introduction of modern electronic money services in the country; which would undeniably have a major effect in the quest of financing development in Lebanon’s crumbling economy. In this respect, the capital control that has heavily emerged in the country since the beginning of 2020 has further paralyzed the e-transactions’ sector. When it comes to sending or receiving money in Lebanon, consumers only have few and expensive options thanks to the country's e-transaction rules, which have helped banks and financial organizations maintain the status quo. We will study to what extent the Lebanese system has had an impact on making Lebanon’s risk profile and regulatory unattractive compared to other countries in the region. Furthermore, there are major challenges of e-transfers in Lebanon today because of the banks’ capital control. In that respect, the purpose of that research is to set a series of recommendations that we believe is crucial to revolutionize the EMT sector in the country and to help boost the Lebanese economy that has exacerbated devastatingly during the last couple of years.